2016
DOI: 10.1155/2016/1785021
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Soluble Interleukin-11 and Interleukin-6 Receptors: A Crucial Function for Proteases during Inflammation

Abstract: The cytokines interleukin-11 (IL-11) and IL-6 are important proteins with well-defined pro- and anti-inflammatory functions. They activate intracellular signaling cascades through a homodimer of the ubiquitously expressed signal-transducing β-receptor glycoprotein 130 (gp130). Specificity is gained through the cell- and tissue-specific expression of the nonsignaling IL-11 and IL-6 α-receptors (IL-11R and IL-6R), which determine the responsiveness of the cell to these two cytokines. IL-6 is a rare example, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 108 publications
2
54
1
1
Order By: Relevance
“…Both the AR42 and [pazopanib + AR42] treatments selected for lower plasma levels of tumor-derived human gp130 and of soluble IL-6RA (Figure 12A). IL-6 in the plasma binds to soluble IL-6RA and this complex has elevated agonist activity at activating tumor cell surface IL-6RA, however, gp130 in the plasma binds to the IL-6/sIL-6RA complex and quenches the ability of the protein complex to act as an agonist [40]. The normal plasma concentration range in a healthy human for gp130 is 200–400 ng/ml and that of IL-6RA is 30–70 ng/ml.…”
Section: Resultsmentioning
confidence: 99%
“…Both the AR42 and [pazopanib + AR42] treatments selected for lower plasma levels of tumor-derived human gp130 and of soluble IL-6RA (Figure 12A). IL-6 in the plasma binds to soluble IL-6RA and this complex has elevated agonist activity at activating tumor cell surface IL-6RA, however, gp130 in the plasma binds to the IL-6/sIL-6RA complex and quenches the ability of the protein complex to act as an agonist [40]. The normal plasma concentration range in a healthy human for gp130 is 200–400 ng/ml and that of IL-6RA is 30–70 ng/ml.…”
Section: Resultsmentioning
confidence: 99%
“…in [21, 39, 40]), rather less attention has been paid to the IL-11R. We have recently shown that the IL-11R has a similar modular organization like the IL-6R [16], and while glycosylation of the IL-6R is described in much detail [25, 41, 42], functional roles for glycans in IL-11 biology have not been analyzed so far.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that the IL-11R can undergo limited proteolysis, predominantly by the metalloprotease ADAM10, and that the resulting soluble IL-11R (sIL-11R) can form an agonistic complex with its ligand IL-11 that is able to activate cells irrespective of their own IL-11R expression [19, 20]. This process, which we have termed IL-11 trans-signaling, closely resembles the trans-signaling pathway of IL-6 [21]. Interestingly, IL-11 trans-signaling is dispensable for fertility and gastric tumor formation in mice [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…The sIL6R is produced mainly through shedding, i.e. limited proteolytic cleavage of the membrane-bound IL6R by the metalloproteinases ADAM17 and ADAM10 (76,77). The receptor is cleaved at the juxtamembrane region (78).…”
Section: The Soluble Interleukin 6 Receptormentioning
confidence: 99%